2018
DOI: 10.5539/hes.v8n3p72
|View full text |Cite
|
Sign up to set email alerts
|

Inside The Gates: First-Generation Students Finding Their Way

Abstract: This paper examines what first-generation students face when coming inside the gates of higher education for the first time, an experience which, without preparation by them and their institution, can disorient them to a level of anxiety which affects their learning. The paper identifies issues arising when they are trying to find their way, such as choosing courses whose content feels foreign, and finding professors who can communicate with them in ways which they understand. It draws upon a review of the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Among the few studies that have been conducted within first-generation students, McGregor et al (1991) found that students with two colleges or university-educated parents reported significantly higher levels of self-esteem than did first-generation students or students with only one college/university-educated parent. First-generation students who attend university without preparation also experience loss of self-esteem (Checkoway 2018). University students' self-esteem is associated with family achievement guilt but this is significantly higher for first-generation students compared to non-first significant generation (Covarrubias et al 2014).…”
Section: Self-esteemmentioning
confidence: 98%
“…Among the few studies that have been conducted within first-generation students, McGregor et al (1991) found that students with two colleges or university-educated parents reported significantly higher levels of self-esteem than did first-generation students or students with only one college/university-educated parent. First-generation students who attend university without preparation also experience loss of self-esteem (Checkoway 2018). University students' self-esteem is associated with family achievement guilt but this is significantly higher for first-generation students compared to non-first significant generation (Covarrubias et al 2014).…”
Section: Self-esteemmentioning
confidence: 98%
“…The study examine what first-generation students face in adjustment when attaining higher education for the first time, an occurrence which, without any prior preparation by them or by their institution (university), may elevate their level of anxiety and may impede in their learning capabilities (Checkoway, 2018). In Pakistan students face a similar dilemma, being first generation students pursuing higher education degrees, is a daunting task.…”
Section: Challenges Of First-generation Students In University Readinmentioning
confidence: 99%
“…This is important to note when helping Brazilian adolescents transition to higher education settings. As many of these adolescents may become first generation college students, it is important that bridging programs note that this population may need additional academic support to help them transition from high school to college (Checkoway, 2018).…”
Section: Activitiesmentioning
confidence: 99%
“…This may also be important to note for educators helping Brazilian adolescents transition from high school to college settings. As suggested by Checkoway (2018), when helping first generation college students transition from high school to college, it can be beneficial to allow students to have an opportunity to take courses that incorporate content from their cultural background.…”
Section: Implications For Promoting Psychological and Academic Wellbementioning
confidence: 99%